Biogeochemical drivers of the fate of riverine mercury discharged to the global and Arctic oceans. Issue 6 (25th June 2015) - Zhang, Yanxu; Jacob, Daniel J.; Dutkiewicz, Stephanie; Amos, Helen M.; Long, Michael S.; Sunderland, Elsie M.
Abstract Rivers discharge 28 ± 13 Mmol yr−1 of mercury (Hg) to ocean margins, an amount comparable to atmospheric deposition to the global oceans. Most of the Hg discharged by rivers is sequestered by burial of benthic sediment in estuaries or the coastal zone, but some is evaded to the atmosphere and some is exported to the open ocean. We investigate the fate of riverine Hg by developing a new global 3‐D simulation for Hg in the Massachusetts Institute of Technology ocean general circulation model. The model includes plankton dynamics and carbon respiration (DARWIN project model) coupled to inorganic Hg chemistry. Results are consistent with observed spatial patterns and magnitudes of surface ocean Hg concentrations. We use observational constraints on seawater Hg concentrations and evasion to infer that most Hg from rivers is sorbed to refractory organic carbon and preferentially buried. Only 6% of Hg discharged by rivers (1.8 Mmol yr−1) is transported to the open ocean on a global basis. This fraction varies from a low of 2.6% in East Asia due to the barrier imposed by the Korean Peninsula and Japanese archipelago, up to 25% in eastern North America facilitated by the Gulf Stream. In the Arctic Ocean, low tributary particle loads and efficient degradation of particulate organic carbon by deltaic microbial communities favor a more labile riverine Hg pool. Evasion of Hg to the Arctic atmosphere is indirectly enhanced by heat transport during spring freshet that accelerates sea ice melt and ice rafting. Discharges of 0.23 Mmol Hg yr−1 from Arctic rivers can explain the observed summer maximum in the Arctic atmosphere, and this magnitude of releases is consistent with recent observations. Our work indicates that rivers are major contributors to Hg loads in the Arctic Ocean.